A Recombinant Acetylcholine Receptor α1 Subunit Extracellular Domain Is a Promising New Drug Candidate for Treatment Of Myasthenia Gravis - Lazaridis, Konstantinos; Fernandez-Santoscoy, Maria; Baltatzidou, Vasiliki; Andersson, Jan-Olof; Christison, Richard; Grünberg, John; Tzartos, Socrates; Löwenadler, Björn; Fribert, Charlotte (Frontiers in Immunology, 2022)
Myasthenia gravis (MG) is a T-cell dependent antibody-mediated autoimmune disease in which the nicotinic acetylcholine receptor (AChR) is the major autoantigen, comprising several T and B cell auto-epitopes. We hypothesized that an efficacious drug candidate for antigen-specific therapy in MG should comprise a broad range of these auto-epitopes and be administered in a noninflammatory and tolerogenic context. We used a soluble mutated form of the extracellular domain of the α1 chain of the AChR (α1-ECDm), which represents the major portion of auto-epitopes involved in MG, and investigated, in a well-characterized rat model of experimental autoimmune myasthenia gravis (EAMG) whether its intravenous administration could safely and efficiently treat the autoimmune disease. We demonstrated that intravenous administration of α1-ECDm abrogates established EAMG, in a dose and time dependent manner, as assessed by clinical symptoms, body weight, muscle AChR content and compound muscle action potential (CMAP) decrement. Importantly, the effect was long-lasting, in contrast to drugs representing current standard of care for MG. The protein had a short plasma half-life, most of what could be recovered was sequestered in the liver, kidneys and spleen. Further, we did not observe any signs of toxicity or intolerability in animals treated with α1-ECDm. We conclude that intravenous treatment with α1-ECDm is safe and effective in suppressing EAMG. α1-ECDm is in preclinical development as a promising new drug candidate for MG.